Exploring a Positive Discipline Approach to Foster Academic Motivation in Senior High School: A Stakeholder Perspective - Hermahayu, Hermahayu; Rasidi, Rasidi; Zahra, Aning Az (Bulletin of Counseling and Psychotherapy, 2025)
This study investigates the perceptions of educators, students, and parents regarding the implementation of positive discipline in schools and its influence on students’ academic motivation. It examines how principals, teachers, students, supervisors, and parents understand and apply positive discipline, including its forms, effectiveness, challenges, and supporting factors. Data were collected through Focus Group Discussions (FGDs) involving 30 participants divided into four stakeholder-based groups. Using thematic analysis, the study found that teachers’ understanding of positive discipline varies, influencing its consistency and effectiveness. Although approaches such as positive reinforcement and reflective group discussions are practiced, punitive methods are still common. The application of positive discipline contributes to improved student motivation, classroom engagement, and healthier school relationships. However, challenges include limited teacher training and occasional resistance from students or parents. Meanwhile, supportive policies and strong communication between schools and parents serve as enabling factors. The study recognizes limitations, such as a relatively small and diverse sample size, which may affect generalizability. Since the research focused on senior high and vocational schools, the findings may not fully represent other educational levels. Moreover, the FGD method may introduce social desirability bias in participants’ responses. Despite these limitations, the findings emphasize the importance of institutional support, continuous teacher development, and parental collaboration in strengthening the practice of positive discipline. This research offers a culturally grounded perspective on positive discipline in Indonesian schools, highlighting its role in fostering student motivation and building a positive educational climate.